1998
DOI: 10.1002/(sici)1099-1409(199807/10)2:4/5<423::aid-jpp116>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Spectroscopic Investigations of Tetra(4-t-butyl)phthalocyano Complexes of Cobalt(II) and Copper(II)

Abstract: The tetra(4-t-butyl)phthalocyanine derivatives of Co and Cu have been studied by ESR spectroscopy in solution owing to their solubility in polar and non-polar solvents. The cobalt complex gives a well-resolved EPR spectrum in toluene glass at 77 K with g = 2.018, g = 2.785, A = 0.0155 cm -1, A = 0.0208 cm -1, P = 0.0201 cm -1 and K = 0.0079 cm Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For the solution forms, the isotropic gfactor (g 0 ), the isotropic hyperfine coupling constant (A 0 ), and the line width coefficients c 0 , c 1 , and c 2 were derived to adjust the amplitude and the line widths of the peaks through the equation L = c 0 + c 1 (m I ) + c 2 (m I ) 2 , [35,36] where L is the line width and m I is the quantum number (m I = − I, − I + 1, . .…”
Section: Epr Studymentioning
confidence: 99%
“…For the solution forms, the isotropic gfactor (g 0 ), the isotropic hyperfine coupling constant (A 0 ), and the line width coefficients c 0 , c 1 , and c 2 were derived to adjust the amplitude and the line widths of the peaks through the equation L = c 0 + c 1 (m I ) + c 2 (m I ) 2 , [35,36] where L is the line width and m I is the quantum number (m I = − I, − I + 1, . .…”
Section: Epr Studymentioning
confidence: 99%
“…The electronic structure of different paramagnetic CoPc complexes has been studied by various spectroscopic means, including electron paramagnetic resonance (EPR) [12][13][14][15][16]. The majority of these investigations were done using continuous wave (CW) EPR and some studies reported conflicting data.…”
Section: Introductionmentioning
confidence: 99%